Prostate-specific membrane antigen-targeting radiopharmaceuticals: a new frontier in hepatic malignancies - Liu, Fucen; Xiao, Liming; Zhao, Ling; Tao, Yi; Huang, Dan; Chen, Zhengguo; He, Chuandong; Wu, Chunyan (Frontiers in Oncology, 2025)
Background/ObjectivesProstate-specific membrane antigen (PSMA) is overexpressed in prostate hypercellularity, making it an effective target for molecular imaging and therapy of prostate cancer. PSMA is expressed in the neovasculature of hepatic malignancies and regulates tumor cell invasion and angiogenesis. The diagnosis and treatment of hepatic malignancies remain challenging. Thus, radiopharmaceuticals targeting PSMA are gaining prominence in the treatment of hepatic malignancies. Therefore, this review aims to discuss the applications of PSMA-targeting radiopharmaceuticals in hepatic malignant tumors, focusing on hepatocellular carcinoma (HCC), to assess their value as a diagnostic and therapeutic agent for hepatic malignancies.MethodsThe potentials of PSMA-targeting radiopharmaceuticals for diagnostic and therapeutic use in hepatic malignancies were investigated. Moreover, their characteristics, diagnostic and therapeutic efficacies, and potential synergies when used in conjunction with other therapeutic modalities were elucidated.ResultsComputed tomography (CT) and magnetic resonance imaging (MRI) are the most common imaging modalities in clinical practice; however, their sensitivity is not optimal. PSMA positron emission tomography/CT can be used as a complementary modality to conventional imaging for characterizing lesions, staging and/or re-staging HCC, and assessing treatment response when conventional imaging results are unclear. Moreover, most patients with HCC are diagnosed at an advanced stage in which treatment options are limited. Hence, PSMA-based radioligand therapy serves as a promising alternative treatment when multiple treatments fail.ConclusionsFurther research and clinical transformation are required to effectively diagnose and treat HCC via PSMA targeting. This will have significant clinical application prospects in primary and secondary hepatic malignancies.